Ethnomedicinal use of vultures by traditional medicinal practitioners in Ghana. (4th May 2019) - Boakye, Maxwell K; Wiafe, Edward D; Ziekah, Meyir Y
Abstract : Vultures form an important ingredient used by traditional medicinal practitioners for the preparation of their therapeutic remedies. The aim of this study was to determine the vulture body parts used for alleviating human ailments by traditional medicinal practitioners in Ghana. Data on the vulture body parts used and human ailments used to alleviate were collected from 28 traditional medicinal practitioners using semi-structured questionnaires. The vulture head, brain, claw, beak, bones and feathers were identified as the body parts used for traditional medicinal purposes. Use values and informant agreement ratio were calculated; the vulture head was found to be the most culturally important body part for treating human ailments, while the feathers had the highest informant agreement ratio. Human ailments that vulture body parts were used to treat include rheumatism, headache, bedwetting and diabetes, while protection against witchcraft was the main spiritual ailment that vulture body parts were used for. This study revealed the high cultural importance of vultures to traditional medicinal practitioners in Ghana. Vulture body parts were particularly important for spiritual ailments that have no orthodox treatment.